Serangan Rusia ke Ukraina Tahun 2022: Perspektif Dilema Keamanan - Fadila, Nur; Yuniarti, Yuniarti (Department of International Relations, Universitas Mulawarman, 2025)
After the collapse of the Soviet Union, relations between Russia and Ukraine have fluctuated, encompassing a period of cooperation that began in 1997 and a period of tension that began in 2004. In 2022, tensions between the two countries reached their peak due to Russia's attack on Ukraine. The research aimed to explain Russia’s attack to Ukraine in 2022 and the reasons behind it. This research is a qualitative and case study research using secondary data extracted by reviewing the literature. The research concept employed in this study was the Security Dilemma concept. The results show that the reason for Russia's attack on Ukraine in 2022 is Russia's security dilemma due to Ukraine's desire to join NATO. If Ukraine joins NATO, Russia feels that its national security will be threatened due to the possibility of building NATO military bases in Ukraine and the loss of Russian influence over Ukraine.